Penerapan Pendekatan Pendidikan Matematika Realistik Indonesia (PMRI) untuk Meningkatkan Hasil Belajar Siswa pada Bilangan Pecahan - Nur Hikma, Ayura; Ilyas, Ilyas (Journal of Comprehensive Science, 2025)
Improving student learning outcomes in fractions is an important aspect that students need to have in mathematics learning, especially today. However, in reality, student learning outcomes in mathematics learning for grade IV MIS Nurul Yaqin students are still low. The Indonesian Realistic Mathematics Education Approach (PMRI) is used as a solution a to improve student learning outcomes because this PMRI approach requires students to be active in the learning process, especially in terms of expressing opinions and discussing. This study uses the Classroom Action Research (CAR) method, with the focus of the study in this study including the learning process and outcomes. This study uses the PMRI approach which consists of four stages. The purpose of this study is to improve student learning outcomes in fractions in grade IV MIS Nurul Yaqin. Based on the results of observaions of student activities in cycle I, the percentage results were 56.82% and increased in cycle II to 77.28% with good qualifications. Based on these data, it shows an increase in residual activity in the application of the PMRI approach in the learning process. Thus, it can be concluded that the application of the PMRI approach is able to improve student learning outcomes in fractions in grade IV MIS Nurul Yaqin.